Preliminary development of assessment tool of leadership style - Siti Fatimah S; Zakira M; Shareza A R; Zainah M; Mazlinda M (Malaysian Journal of Medicine and Health Sciences, 2020)
Leadership is hard to define, but it’s easy to recognize. Leaders know that to lead they must keep up their leadership skills. Effective leadership skills required from nurse managers which include the ability to create an organization culture that combines high-quality health care and patient/employee safety with highly developed collaborative and team-building skills. This paper presents the preliminary study of the development of the assessment leadership tool emphasising on the process of validation and implementation of necessary steps in tool development. Methods: Questionnaires on leadership style was adopted from Northouse (2014) and working motivation from Purohit et al., (2016). Modification for leadership styles from 35 modified into 48 question and tool on nurses’ motivation from 19 items modified into 28 items. Developed questionnaires were finalized with literature guidance and two content experts. A pre- test was done with 30 respondents for each set of questionnaires. Results: Preliminary development of tool Reliability test result shown that for leadership styles questionnaires which are consisted of 48 items is (α = 0 .77) and working motivation consisted of 28 items is (α = 0.70). Minor modification needed after the literature searching and analysis of pre-test stage, the discussion with expert person after they go through the questionnaires also suggested some additional info are needed. After doing validation process the questionnaires are more stable and valid to use for the author target group. Conclusion: These leadership styles assessments are beneficial to guide nurse managers to use suitable styles to manage their nursing staffs. Assessment on working motivation among nurses is also recommended to overcome the issues on working retention among them. In future further investigation regarding which appropriate leadership style need to be explored and the level of working motivation among nursing staff should be monitored regularly.